Navigating a New Normal: A Mixed-Methods Study of the Pediatric Tracheostomy Parent-Caregiver Experience - Laine DiNoto; Adrianne Frankel; Taylor Wheaton; Desirae Smith; Kimberly Buholtz; Rita Dadiz; Kathryn Palumbo (Children)
Objective: To explore the experiences and self-efficacy of parent-caregivers providing care for a child with a tracheostomy tube. Study Design: Parent-caregivers completed surveys and participated in semi-structured interviews about their experiences learning to care for their child with a tracheostomy tube. Survey data were analyzed using descriptive statistics. Interviews were transcribed verbatim and analyzed thematically through coding. Results: Fifteen parent-caregivers participated in the survey, 13 of whom completed an interview. After receiving a tracheostomy, children were hospitalized a median of 6 months prior to discharge home. At the time of our study, children had been home for a median of 3.5 years. Parent-caregivers felt more prepared to perform routine daily care compared to triaging a change in medical status. Parent-caregiver self-efficacy in performing tracheostomy care skills improved with experience at home. Four themes were identified from interviews: new identity formation, enduring education, child and family biopsychosocial support, and establishing normalcy. Parent-caregivers shared that education was more than just acquiring skills; it also involved discovering diverse ways of learning and building confidence in one’s own abilities to fulfill the many types of roles they serve to successfully care for and keep their child safe while supporting their social and emotional needs as parent-caregivers. Conclusions: Parent-caregivers’ reflections on their experiences provide critical insight into their psychosocial needs and challenges in providing care to children with tracheostomies. Further investigation of lived experiences is vital to shaping a community that can support families of medically complex children.